2013
DOI: 10.1038/eye.2013.163
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of manual vs automated disc margin delineation using spectral-domain optical coherence tomography

Abstract: Aims To examine the impact of manual vs automated disc margin delineation on optic nerve head (ONH) and retinal nerve fiber layer (RNFL) parameters using spectraldomain optical coherence tomography (SDOCT). Methods A prospective cohort study consisting of normal, glaucoma suspect (GS) and glaucoma patients who underwent ONH and RNFL measurements using SDOCT technology (RTVue; Optovue Inc.). The retinal pigment epithelium/Bruch's membrane (RPE/BM) complex end points were automatically determined first, and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…In an ideal situation, it is preferable to have a large number of same-day repeat sessions on a single eye to evaluate the SSI effect. Additionally, factors other than signal intensity, such as cataract, vitreous floaters, or disc margin delineation algorithm failure, 29 may impact measurement values and lead to increased variability independent of SSI. It also is unknown to what extent measurement variability caused by extreme high and low SSI values affects OCT diagnostic classifications (i.e., green/yellow/red color code), which may complicate interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…In an ideal situation, it is preferable to have a large number of same-day repeat sessions on a single eye to evaluate the SSI effect. Additionally, factors other than signal intensity, such as cataract, vitreous floaters, or disc margin delineation algorithm failure, 29 may impact measurement values and lead to increased variability independent of SSI. It also is unknown to what extent measurement variability caused by extreme high and low SSI values affects OCT diagnostic classifications (i.e., green/yellow/red color code), which may complicate interpretation.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 31 On the other hand, 2D peripapillary RNFL thickness and 2D neuroretinal rim measurements generated along a flat reference plane (e.g., cup-to-disc ratio and rim area) on average undergo significant changes after correction of segmentation errors. 17 , 23 , 24 , 40 , 43 The need to manually fix errors or repeat scans in the clinic requires extra time and attention, and parameters derived from 3D volume scans appear to reduce this need.…”
Section: Discussionmentioning
confidence: 99%
“…10,16 Recent studies have examined the agreement between automated and manual segmentation in their derivation of disc margin-based measurements such as cup-disc ratio, with the assumption that the termination of the Bruch's membrane/retinal pigment epithelium complex represents the clinical disc margin. 19,20 While these studies have reported generally good agreement between the two methods, the clinically visible optic disc margin seldom corresponds to BMO, 6 making these studies challenging to interpret. In contrast, our evaluation of the automated segmentation algorithm compared automated and manual ILM and BMO segmentation in all of the same B-scan images.…”
Section: Discussionmentioning
confidence: 99%
“…Automated segmentation of the ILM and Bruch's membrane, including BMO, 10,16 is currently used in commercial SD-OCT devices. 17,18 To date, published studies have been limited to reporting the agreement between manual and automated segmentation methods primarily for deriving traditional indices such as cup-disc ratio and rim area, 10,16,19,20 with the assumption that BMO represents the disc margin. The aim of our study was to quantify and characterize the differences between an automated segmentation algorithm and manual methods to identify the ILM and BMO.…”
mentioning
confidence: 99%